Classification of the agitation level based on facial variation for icu patients in hospital - Muhammad Naufal Mansor (School of Mechatronic Engineering, Universiti Malaysia Perlis, 2011)
There is a lack of commercial technologies under the generic topic of monitoring a patient in Intensive Care Unit (ICU). This answers too many of the misjudged problems. In this research, one approach to Human Computer Interface (HCI) for monitoring patient is presented. In this dissertation, the design and development of intelligent monitoring system for facial expression analysis of patients in ICU is proudly presented. The ICU patients can be in coma or the patients may be under sedation due to surgery. The facial movements need to be monitored by the nurses at selected intervals and reported to doctors for possible further treatments. Detection of facial changes is very crucial for further treatment. In this research, our study only limit on the eyes and mouth motions. A study is also made on varied illumination levels on the face of patient. The purposed monitoring scheme is to be robust within selected levels of illumination on the face of patient.